Clinical and Genetic Diversity of PMP22 Mutations in a Large Cohort of Chinese Patients With Charcot-Marie-Tooth Disease - Liu, Xiaoxuan; Duan, Xiaohui; Zhang, Yingshuang; Fan, Dongsheng (Frontiers in Neurology, 2020)
Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous group of inherited neuropathies. The purpose of this study is to identify the clinical and genetic diversity of peripheral myelin protein 22 (PMP22) in Chinese patients with CMT disease and evaluate their correlations with the clinical manifestations. Using the multiplex ligation-dependent probe amplification (MLPA) technique and Sanger sequencing of PMP22 in a cohort of 465 Chinese families between 2007 to 2019, we identified 137 pedigrees with PMP22 duplications (29.5%), 26 pedigrees with PMP22 deletions (5.6%), and 10 pedigrees with point mutations (2.2%). By comparing our data with the results from other CMT centers in China, we estimate that the frequency of PMP22 mutation in mainland China is approximately 23.3% (261/1120). We confirmed de novo mutations in 40% (4/10) of PMP22 point mutations. We have also identified two severely affected patients who are compound heterozygotes for recessive PMP22 mutations (novel mutation c.320-1 G>A and R157W mutation) and a 1.5 Mb deletion in 17p11.2-p12, suggesting that c.320-1 G>A might be another recessive allele contributing to DSS in addition to the T118M and R157W mutations. A de novo mutation of S79P in PMP22 was also identified concomitantly with the R94W mutation in mitofusin2 (MFN2). Our study highlights the phenotypic variability associated with PMP22 mutations in mainland China. The results provide valuable insights into the current strategy of genetic testing for CMT disease. NGS technology has increased the potential for efficient detection of variants of unknown significance (VUS) and concurrent causative genes. Greater cooperation between neurologists and molecular biologists is needed in future investigations.